Efficacy of Parenteral Granisetron in the Prevention of Post-Operative Nausea and Vomiting (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Post-operative nausea and vomiting (PONV) is one of the most unpleasant complications following anaesthesia and surgery since long time. A non -randomized case control study of prevention of post operative nausea and vomiting with IV- Granisetron was done on 270 adult surgical patients who received general or spinal aneasthesia. All the patients were followed up to 48 hours after operation. A complete response was achieved in prophylaxis group as 92.6% and in control group as 90.4%(p-value=0.6637). In patient with PONV ,gender incidence is equal in prophylaxis group. Female incidence is higher in control group. Majority of patients (90 to 100 %) had PONV within 24 hours after operation. As there is insignificant difference in the achievement between prohylaxis group and control group, anti emetic prophylaxis is recommended only for patient with one or more risk factors for PONV. DOI:10.3329/jbcps.v27i3.4290 J Bangladesh Coll Phys Surg 2009; 27: 139-143